Apolipoprotein E Affects In Vitro Axonal Growth and Regeneration via the MAPK Signaling Pathway. Issue 6 (June 2019) - Yin, Cheng; Guo, Zong-duo; He, Zong-ze; Wang, Zhen-yu; Sun, Xiao-chuan
Following central nervous system injury in mammals, failed axonal regeneration is closely related to dysneuria. Previous studies have shown that the obvious effects of apolipoprotein E (ApoE) on traumatic brain injury (TBI) were associated with an axonal mechanism. However, little information on the actions of ApoE and its isoforms on axonal regeneration following TBI was provided. In our study, the cerebral cortices of ApoE-deficient (ApoE -/- ) and wild-type (ApoE +/+ ) mice were cultured in vitro, and an axonal transection model was established. Interventions included the conditioned medium of astrocytes, human recombinant ApoE2/3/4 isoforms and inhibitors of the JNK/ERK/p38 pathway. Axonal growth and regeneration were evaluated by measuring the maximum distance and area of the axons. The expression levels of β-tubulin III, MAP2, ApoE, p-JNK, p-ERK and p-p38 were detected by immunofluorescence and western blotting. The results showed that ApoE mRNA and protein were expressed in intact axons and regenerated axons. Axonal growth and regeneration were attenuated in ApoE -/- mice but recovered by exogenous ApoE. Human recombinant ApoE3 positively influenced axonal growth and regeneration; these effects were mediated by the JNK/ERK/p38 pathway. These results suggest ApoE and its isoforms may have influenced axonal growth and regeneration via the MAPK signaling pathway in vitro.